Efek Inhibitor Proteasom Terhadap Gambaran Histopatologi Jantung pada Tikus yang diinduksi Aterosklerosis - Ilhami Romus; Ismawati Ismawati; Indah Putri Arwandi (Fakultas Kedokteran Universitas Riau, 2023)
Proteasome inhibitors are compounds that can inhibit the proteasome pathway in carrying out its functions. Proteasome inhibitors have a beneficial effect due to their anti-inflammatory properties. The proteasome inhibitor used in this study was bortezomib. This study aimed to analyze the effect of proteasome inhibitors on cardiac histopathology in atherosclerosis-induced rats. This study used male Rattus novergicus Wistar strain which was divided into 3 groups, namely the control group, the atherosclerosis-induced group and the atherosclerosis-induced group and given bortezomib. The results obtained the mean scores of edema, inflammation and necrosis in the atherosclerosis group were given bortezomib at a dose of 50 g/kgBW were less than the atherosclerosis group. Theese difference were statistically significant (p<0.05). This study concluded that the administration of bortezomib can reduce the Impact of atherosclerotic lesions on the heart muscle.